Effect of Slow Breathing Exercise on Time Domain Heart Rate Variability in Transfusion Dependent Thalassemic Patients - Das, Kamol Chandra; Ferdousi, Sultana; Urmi, S F H; Mostafa, Musfika; Tonni, Shomia Farid (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Time domain measure of heart rate variability (HRV) is a newersystem to seek out any alteration in cardiac autonomic nerve function (CANF) in transfusion dependent thalassemic (TDT) patients. Slow breathing exercise (SBE) plays important role in improvement of HRV in health and various diseases.This research aims to observe the effect of slow breathing exercise (SBE) on time domain measures of HRV in TDT patients. This prospective interventional study was done in the Department of Physiology, Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka in 2018 on 60 male TDT patients aged 15-30 years. Thirty patients received conventional treatment and 30 patients performed slow breathing exercise along with the conventional treatment for 3 months. Age and sex matched healthy control were taken to compare. All subjects were followed up at baseline and after 3 months. Time domain HRV parameters were recorded by Power Lab 8/35. For statistical analysis paired sample 't' test and independent sample 't' test were done. Mean RR interval, Mean SD, RMSSD and pRR 50% were found significantly lower in TDT patients compared to healthy control at baseline and on the other hand mean heart rate was significantly higher in this group of patients. After 3 months of slow breathing exercise, significant decrement of mean heart rate and significant increment of others parameters occurred with trend of improvement in cardiac autonomic nerve function in TDT patients. In conclusion slow breathing exercise may improve cardiac autonomic nerve function and sympathovagal balance in transfusion dependent thalassemic patients. Bangabandhu Sheikh Mujib Med. Coll. J. 2022;1(2):65-69